Influence of post-bleaching time on a composite resin bond strength to enamel - Baldión-Elorza, Paula Alejandra (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: despite the aesthetic advantages of tooth whitening, it has been shown to alter the adhesion of composite resins to enamel—a process determined by the residual concentration of oxygen-free radicals on the enamel’s surface and subsurface due to degradation of the bleaching agents’ hydrogen peroxide—. The goal of this study was to evaluate the effect of hydrogen peroxide on a composite resin’s bond strength to enamel in different time intervals after whitening. Methods: 90 human premolars were selected and sorted out in 6 groups: the control group, which was subjected to the adhesive technique only, and five study groups treated with the bleaching agent and each of them being later subjected to the adhesive technique at different time intervals after whitening (0, 1, 7, 14, and 28 days), in order to determine the shear bond strength of the resin adhered to enamel. The obtained data were analyzed by means of the ANOVA test with the F statistical test and Fisher & Duncan multiple comparisons, using p values of <0.05 as statistically significant differences. Results: the groups undergoing bleaching from 0 to 28 days presented adhesion values statistically lower than those of the control group. Conclusions: hydrogen peroxide reduces the values of adhesion to enamel. Post-bleaching time is crucial to recover the composite resin bonding strength to dental structure.